An improved fast decoupled power flow model considering static power–frequency characteristic of power systems with large‐scale wind power. Issue 2 (March 2014) - Duan, Yao; Zhang, Buhan
Abstract Large‐scale wind power (LSWP) integration may cause significant impact on power system frequency, so it is necessary to take frequency regulation issues into account in power system steady‐state operation analysis. An improved fast decoupled power flow model considering static power–frequency characteristic of power systems with LSWP is proposed in this paper. In this scheme, the active power of generators and loads are presented with their static power–frequency characteristics. The slack bus degenerates to the nodal voltage phase angle reference bus of the system, and all the generators with frequency regulation capability participate in unbalanced power regulation. The power flow calculation results can reveal the impact to the system frequency of operation mode change and load variation, and present the output adjustment of the generators. The proposed model can be solved conveniently by the block solving technology based on the fast decoupled power flow algorithm. The scheme presented in this paper has been tested on the IEEE standard 30‐bus test system by simulating basic operation and primary and secondary frequency regulation of the generators, which demonstrated the validity by the method. © 2014 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.